Upaya Meningkatkan Hasil Belajar UPAYA MENINGKATKAN HASIL PEMBELAJARAN LOMPAT JAUH MELALUI PENDEKATAN BERMAIN LONGU PADA SISWA KELAS V SD NEGERI 035 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2021 - Delpina Pasaribu (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
The implementation of the long jump learning for fifth grade students at SD N 035 Tarai Bangun, Tambang District, Kampar Regency was not satisfactory for physical education teachers, the results obtained by students in the final evaluation test of learning were still many students whose scores did not meet the standards of the Minimum Completeness Criteria (KKM) that had been set. While the purpose of this research is to make learning more effective by using a kangaroo jump approach or by varying various kinds of games into learning. Based on the problems above, the researcher concludes the formulation of the problems faced by the researchers, namely "Whether through the kangaroo jumping game approach as learning can improve long jump learning outcomes in fifth grade students of SD Negeri 035 Tarai Bangun in the 2021 academic year. The results of research using 2 cycles and 4 meetings shows in the first cycle the average final grade of 71.9 with a percentage value of 76% completeness the value is still unsatisfactory. Then continued in the second cycle, the final average value of the class was 75.04 with a percentage value of 95.2%, the value produced was as desired. Based on the research, it can be concluded that through the approach of playing kangaroo jump in the long jump material using aqua bottles and pralon media as learning facilities and infrastructure, there has been an increase in learning outcomes for fifth grade students of SD Negeri 035 Tarai Bangun, Tambang District, Kampar Regency. Suggestions from researchers include several things, namely: it is expected that physical education teachers in elementary schools use Classroom Action Research (CAR) in learning, teachers can vary various forms of games in learning, and aqua bottles and pralon media can be used to overcome the lack of teaching aids in teaching and learning. long jump learning.